TRANSFORMATION LEADERSHIP IN VIRTUAL TEAMS - L. V. Kozhevnikova; I. E. Starovoytova (Вестник университета, 2021)
The article is devoted to a new model for organizing production activities that is adequate to the challenges of digitalization – virtual organizations. The authors show that the widespread adoption of virtual organizations that have no clear boundaries in space and time over the past decade gives rise to new management problems. Old management models based on hierarchy, authoritarian approach, and punishment / reward as the main motivators are not effective in virtual teams. Traditional transactional leadership should be replaced by transformational leadership, which involves an individual approach, intellectual stimulation, idealized influence and inspiring motivation. The authors indicate the social and psychological difficulties of the spread of transformational leadership. The paper emphasizes the need for the formation of leadership, managerial and digital competencies for effective leadership in project virtual teams.